Manajemen Strategi Ekonomi pada Lembaga Pendidikan Islam - Ivan Riyadi (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2019)
This article is written based on unique considerations in theworld of education and economic strategies in Islamic educational institutions. This research proposes a strategic framework that can help evaluate the relationship and linkages between economic strategies and Islamic education institutions. The evaluation is expected to be a material consideration in the management of economic strategies, so that the performance of Islamic education institutions can be improved. Institutional performance is evaluated using criteria that include productivity, cost reduction, innovation, reactivity, responsiveness, and collaboration. To get a complete picture in this article, a qualitative approach with the study of literature is used. The results of the study show that evaluating the relationship of economic strategy management in Islamic education institutions uses a framework. management functions include; planning, organizing, directing and controlling. Therefore, management is defined as the process of planning, organizing, leading, and controlling the efforts of the organization with all its aspects so that organizational goals are achieved effectively and efficiently.